Antibacterial bio pores as a river flow filter for the development of "Ndeso Park" water tourism - Nur Anita Yunikawati; Lustina Fajar Prastiwi; Magistyo Purboyo Priambodo; Lutfi Asnan Qodri (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
The realization of the full potential of natural resources in each village for the benefit of the local community has been observed as a significant challenge. The national village-owned enterprises program encourages villages to optimize the utilization of their existing natural and human resources with the objective of fostering their economic independence. The program entails the optimization of the national village-owned enterprises program in the tourism sector, specifically in the context of Taman Ndeso. The objective of this community service activity is to provide technological assistance and address the issue of river water filtration as a pool water source. The impetus for this activity is the declining tourism activities at Taman Ndeso due to the presence of turbid water in the pool, which was deemed unsuitable for use. The activity is realized through the construction of a water purification filtration system to produce clean and healthy water. Â The antibacterial biopores are applied as filtration technology. This technology is designed to capture bacteria from river water that flow into the pond. This research adopted the direct exploration method, which was divided into a number of stages, including planning and preparation, implementation, evaluation, and reporting. The research outcome manifests into the restoration of the Taman Ndeso water tourism pool, which will be capable of attracting tourists and reviving village income to the maximum extent possible, with the management of the village-owned business entity.